Diary of a strategic teacher: complex constitution in teaching in art (Revista de Ensino em Artes, Moda e Design, 2024)
Based on theoretical interlocutions with complex thinking, proposed by Edgar Morin, the article will analyze the process of complex constitution of a teacher, based on excerpts from her logbook, in order to verify her strategic actions in the face of doubts and uncertainties, resulting from the educational process in the early years of elementary school. The strategies found in imagination and laughter in Gianni Rodari (1982), served as a bet on complex didactic action in the learning of drawing. As a textual genre, the diary will be mobilized as a rhythmic counterpoint, between past and present, since the narrative voice will be made in the first person, distanced only by the temporal interval between before and now.
Keywords: complexity; teaching action; teaching of visual arts